UJI DAYA HAMBAT SEDIAAN TONER WAJAH INFUSA DAUN BELIMBING WULUH (Averrhoa bilimbi L.) TERHADAP Propionibacterium acnes: UJI DAYA HAMBAT SEDIAAN TONER WAJAH INFUSA DAUN BELIMBING WULUH (Averrhoa bilimbi L.) TERHADAP Propionibacterium acnes - burhamin, yusriyani (Akademi Farmasi Yamasi Makassar, 2025)
. This research has been made with the objective to determine at what concentration the infusa of bilimbi leaves (Averrhoa bilimbi L.) in the form of facial toner preparations can inhibit Propionibacterium acnes bacteria optimally. The method used in this research is a laboratory experimental method by testing the inhibition of toner preparations. Belimbing wuluh leaves were extracted using the infusa method then made facial toner preparations with concentrations of 10%, 20% and 30% and tested with the paperdisk method. From the results of the research on the inhibition of facial toner preparations of infusa extract of bilimbi leaves (Averrhoa bilimbi L.) showed that at concentrations of 10% and 20% could not inhibit the growth of Propionibacterium acnes bacteria. Meanwhile, the 30% concentration can inhibit the growth of Propionibacterium acnes bacteria optimally optimally with the inhibition zone around the paperdisk.